Noninvasive Monitoring during Interhospital Transport of Newborn Infants - Georg M. Schmölzer; Megan O’Reilly; Po-Yin Cheung (Critical Care Research and Practice, 2013)
The main indications for interhospital neonatal transports are radiographic studies (e.g., magnet resonance imaging) and surgical interventions. Specialized neonatal transport teams need to be skilled in patient care, communication, and equipment management and extensively trained in resuscitation, stabilization, and transport of critically ill infants. However, there is increasing evidence that clinical assessment of heart rate, color, or chest wall movements is imprecise and can be misleading even in experienced hands. The aim of the paper was to review the current evidence on clinical monitoring equipment during interhospital neonatal transport.